Wastewater treatment from nitrogen compounds - Semenova, Olena; Bublienko, Natalia; Suleyko, Tetiana; Reshetnyak, Lyudmila (My University, 2020)
Increasing the concentration of nitrogen compounds in wastewater has led to a deterioration of surface water quality, which is the main source of economic drinking water supply for the vast majority of Ukrainians. The Government of reservoirs in the territory of Ukraine recorded an excess of norms for ammonia nitrogen – 2 – 15 times, nitrates – 7 – 20 times. The consequences of contamination with nitrogen compounds are eutrophication, which is caused by hypertrophied development of algae («flowering»); reducing oxygen content. We have proposed biological sewage treatment with this type of contamination.
Keywords: wastewater; nitrogen-containing compounds; activated sludge; biochemical purification; стічні води; азотовмісні сполуки; активний мул; біохімічне очищення; кафедра екології та екоменеджменту; кафедра біотехнології і мікробіології